Factors associated with the non-use of modern contraception in the Djougou-Copargo-Ouaké health zone in 2024 - M.K. Zinvokpodo; A. Noudamadjo; R.C.S. Zinvokpodo; J.G.N.K. Tchilamessi (European Scientific Journal, ESJ, 2025)
Introduction: Family planning remains underutilized in sub-Saharan Africa, despite its contribution to reducing maternal and infant mortality. In Benin, the prevalence of modern contraception among women in union increased from 3% in 1996 to 12% in 2017-2018, according to the EDSB-V, a progress still insufficient to reach optimal coverage. This study aims to identify the factors explaining the low use of modern contraceptive methods in the Djougou-Copargo- Ouaké health zone. Materials and methods: A descriptive and analytical cross-sectional study with prospective data collection was carried out among women of childbearing age (15-49 years) residing in this health zone and meeting the inclusion criteria. A multivariate analysis was performed to identify factors associated with non-use of modern contraceptive methods. Results: The prevalence of use of modern contraceptive methods was 12.01%. Several factors were associated with low use of modern contraceptive methods: desire to have children (OR = 0.039; p= 0.001), low level of knowledge about contraceptive methods (OR = 1.88; p = 0.048), lack of awareness of their benefits (OR = 25.93; p = 0.001) and no experience of unwanted pregnancy (OR= 2.07; p = 0.039). Conclusion: These results underline the need to raise awareness of modern contraception and to promote the enrolment and retention of young girls in the education system in order to improve their access to contraceptive methods and promote better family planning.